Aquaculture : a component of low cost sanitation technology - Edwards, Peter (The World Bank Washington DCUS, 1985)
Discusses all phases of aquaculture, including commercial viability, sanitary and biological considerations, public health, financial economic and sociological aspects. Current studies are detailed and options are discussed for their potential applicability to developing countries, considering requirements for capital and labour skills as well as physical needs such as land.